"Baltic Power" Energy Transition, Management of Renewable Energy Sources In Poland - Magdalena FILIPOWICZ (Communications of International Proceedings, 2024)
The article takes up the topic of wind power plants in the Baltic Sea. Currently, many such investments are being built, as experts estimate the region's potential at 85GW. The paper reviews the achievements of wind power in Poland to date and forecasts their future development. It also highlights the impact of these solutions on the local community, environment and economy of the region. The article points out that wind farms in the Baltic Sea can play an important role in Poland's energy transition. It reviews data from the Central Statistical Office (CSO) and the Ministry of Climate, from which it is clear that this energy sector is on an upward trend and worth investing in. One investment was selected which will be the first to be implemented and described in detail.
Keywords: offshore wind energy; energy transition in Poland; renewable energy sources